Bausung Bridal Tradition of Banjar Traditional Wedding Brides in ‘Urf Perspective - Salim W, Rio; J, Jamilah (Sakina: Journal of Family Studies, 2022)
Bausung bridal tradition is one of a traditional wedding processions of Banjar society. Bausung bridal is lifting or carrying the bride and groom up on the shoulders of two men. The society belief if this tradition did not carried out they will get a sanction from their ancestors. The purpose of this research is to analyze this tradition deeply to find out the Bausung bridal tradition in the composition of Islamic legal rules according to the perspective of 'urf. This research is an empirical that has qualitative approach. Data source to be used are primary as and secondary data. The results of this study indicate that the Bausung bridal tradition is classified as 'urf amali in terms of 'urf material because it is focuses on a practice, in terms of the scope of 'urf is 'urf khaas because it is only carried out by the Banjar tribal society and in terms of the validity of 'urf is 'urf shahih because the majority of the process of the Bausung bridal tradition does not conflict with Islamic law, although there are still some practices from this tradition that must be abandoned because it has the potential to cause shirk to Allah SWT.